Assessing sleep using hip and wrist actigraphy - Slater, J.; Botsis, T.; Walsh, J.; King, S.; Straker, Leon; Eastwood, Peter (Blackwell Publishing, 2015)
© 2015 Japanese Society of Sleep Research. Wrist actigraphy is commonly used to measure sleep, and hip actigraphy is commonly used to measure activity. It is unclear whether hip-based actigraphy can be used to measure sleep. This study assessed the validity of wrist actigraphy and hip actigraphy compared to polysomnography (PSG) for the measurement of sleep. 108 healthy young adults (22.7±0.2 years) wore hip and wrist GTX3+ Actigraph during overnight PSG. Measurements of total sleep time (TST), sleep efficiency (SE), sleep onset latency (SOL) and wake after sleep onset (WASO) were derived and compared between wrist actigraphy, hip actigraphy and PSG. Sensitivity, specificity and accuracy of wrist actigraphy and hip actigraphy for each variable were derived from epoch-by-epoch comparison to PSG. Compared to PSG: TST and SE were similar by wrist actigraphy but overestimated by hip actigraphy (both by 14%); SOL was underestimated by wrist actigraphy and hip actigraphy (by 39 and 80%, respectively); WASO was overestimated by wrist actigraphy and underestimated by hip actigraphy (by 34 and 65%, respectively). Compared to PSG the sensitivity, specificity and accuracy of wrist actigraphy were 90, 46 and 84%, respectively; and of hip actigraphy were 99, 14 and 86%, respectively. This study showed that using existing algorithms, a GTX3+ Actigraph worn on the hip does not provide valid or accurate measures of sleep, mainly due to poor wake detection.